Aligning Human Resource Information Systems (HRIS) with the Imperatives of Society 5.0: A Strategic Framework for Digital Talent Management in the Indonesian Banking Sector - Lia Ovi Arini; Dessy Nur Ardillah; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2025)
The rapid acceleration of digital transformation, spurred by the global pandemic and new economic demands, has placed the Indonesian banking sector at a critical juncture. Amidst this disruption, the Society 5.0 paradigm has emerged as a human-centric vision, proposing a deep integration of technology and society to enhance the quality of life. However, the success of this transformation hinges on its most vital asset: digital talent. A significant gap currently exists between the strategic capabilities of modern Human Resource Information Systems (HRIS) and the imperative to effectively manage digital talent in alignment with Society 5.0. This research aims to bridge this gap by developing a comprehensive conceptual framework, titled